Community Participation in Combating Money Politics Practices in Murtigading Village, Yogyakarta - Rahayu Werdiningih, Sri; Prasetyoningsih, Nanik (PT. Multidisciplinary Press Indonesia, 2025)
Murtigading Village, located in Sanden District, Bantul Regency, has achieved notable success in combating money politics in the village chief elections (Pilurdes), general elections, and regional elections. This study explores how the community of Murtigading mobilized a movement to counter money politics, identifies the key factors contributing to the movement’s success, and examines strategies to ensure the sustainability of this anti-money politics effort. Employing a qualitative descriptive approach, the research collected primary and secondary data through observations, literature review, and interviews with key movement initiators and members of the Bantul Regency Election Supervisory Committee (Bawaslu). The findings reveal that the anti-money politics movement in Murtigading significantly contributed to the reduction and eventual eradication of money politics practices in the village during the 2019 and 2020 elections. Two primary factors influenced this success: the presence of community leaders as catalysts and active community participation. To maintain the movement’s momentum, continuous promotion and internalization of anti-money politics values through political literacy and socialization are essential. This study highlights the critical role of community-driven initiatives in fostering clean electoral processes and strengthening democratic governance at the grassroots level.